2021
DOI: 10.1245/s10434-021-10079-x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Recovery After Surgery can Improve Patient Outcomes and Reduce Hospital Cost of Gastrectomy for Cancer in the West: A Propensity-Score-Based Analysis

Abstract: Background Data on ERAS for gastrectomy are scarce, and the majority of the studies come from Eastern countries. Patients in the West are older and suffer from more advanced tumors that impair their clinical condition and often require neoadjuvant treatment. This retrospective study assessed the feasibility and safety of an Enhanced Recovery After Surgery (ERAS) protocol for gastrectomy in a Western center. Methods We conducted a single-center study of 351… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 22 publications
2
14
0
Order By: Relevance
“…Due to this, we considered our findings as appropriate to be compared though the total number of procedures in the two periods were uneven. A decrease in costs using ERAS protocol by comparing two periods as we used in this study has been reported as well, which is consistent with our findings 12 , 20 .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Due to this, we considered our findings as appropriate to be compared though the total number of procedures in the two periods were uneven. A decrease in costs using ERAS protocol by comparing two periods as we used in this study has been reported as well, which is consistent with our findings 12 , 20 .…”
Section: Discussionsupporting
confidence: 93%
“…Various studies which compared costs with or without ERAS multimodal protocol showed the same with international currencies such as Euros, British Pounds, or Swiss Francs. 12 , 18 , 20 The overall results seem to agree that changing traditional to modern perioperative care may decrease costs and postoperative morbidity.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The use of PSM (propensity score matching) analysis in our clinical study allowed for a good correction of selectivity bias, which was confirmed in many previous studies [ 18 21 ]. SPSS used version 22.0 (SPSS, Inc., Chicago, IL, USA), and P value < 0.05 was considered statistically significant.…”
Section: Methodssupporting
confidence: 71%
“…However, ERAS programs have also proven to be effective after open surgery with a reduction of postoperative infections [ 10 ] and acceleration of patients’ postoperative recovery [ 8 , 26 ]. The applications of ERAS programs, in patients treated with open surgery, can improve patients’ recovery and reduce hospital costs without increasing readmission or the need for postdischarge care [ 25 ].…”
Section: Discussionmentioning
confidence: 99%